2023
DOI: 10.3390/foods12173255
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mortality from Cardiovascular Diseases and Total Drinking Water Hardness: Systematic Review with Meta-Analysis

Aleksandra Bykowska-Derda,
Marcin Spychala,
Magdalena Czlapka-Matyasik
et al.

Abstract: Background: Interest in water chemical activity, its content, and its impact on human health has greatly increased throughout the last decade. Some studies suggest that drinking water with high hardness may have preventative effects on cardiovascular diseases. This study aims to investigate the association between drinking water hardness and cardiovascular disease (CVD) mortality. Methods: The study selection process was designed to find the association between drinking water hardness and CVDs mortality. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In this way, water that complies with regulatory standards can have very low calcium concentration and be corrosive. Although previous epidemiologic studies have suggested an inverse relationship between water hardness and cardiovascular mortality, mainly determined by concentrations of calcium and magnesium, often drinking water guidelines do not base recommended hardness or TDS on health outcomes [41][42][43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, water that complies with regulatory standards can have very low calcium concentration and be corrosive. Although previous epidemiologic studies have suggested an inverse relationship between water hardness and cardiovascular mortality, mainly determined by concentrations of calcium and magnesium, often drinking water guidelines do not base recommended hardness or TDS on health outcomes [41][42][43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%